Otimização na preparação do painel de análises financeiras em Power BI/Excel: estudo de caso na área de controladoria - Laurentino, Pamela de Almeida (2021)
The case study presented was carried out in a chemical company and aimed at the challenge of reducing the time to update monthly data from a financial analysis report of the production plant developed by the controllership area. Based on the proposal to extend the dedication to analysis, comments and identification of irregularities, the optimization in the preparation of files was encouraged. The panel update time can be separated into two destinations: the first would be data collection followed by the feeding of the bases and modification of the panel elements that happens every month; the second is about the verification and validation of data according to its sources, thus ensuring consistency of information. With the work developed, results can be obtained on both fronts, since the optimization addressed, from a linguistic point of view, is the creation of more favorable conditions for a process which, in this case, involves continuous improvement together with the automation of repetitive activities. It is also important to mention the use of SAP software (System Applications and Products) for direct and indirect data extraction, due to the use of corporate reports which were, using this tool, used in parallel by other areas and which were also used in this process. Together, the process of automating the data extraction from the SAP tool was developed using the Python programming language. All work was carried out in phases that should continue to take place due to the wide area of study.